2015
DOI: 10.2495/bem380141
|View full text |Cite
|
Sign up to set email alerts
|

Engineering optimization with the fast boundary element method

Abstract: A wide variety of engineering design tasks can be formulated as optimization problems where the shape and topology of an elastic domain are optimized to reduce costs, e.g. global compliance, while satisfying certain constraints, such as volume constraint. We propose an application of a fast 3D boundary element code to the problems of shape and topology optimization. Our algorithm is based on the formalism of topological derivatives. Adaptive tree strategy of sampling of topological derivatives inside the domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The level of details in the final solution depends on the threshold of the topological derivative and the number of iterations. However, both obtained solutions are in qualitative agreement with 2D and 3D solutions of similar problems obtained earlier [15,16,23]. The quality of the surface of the optimal configuration is improved with Laplassian smoothing [24] post-processing step.…”
Section: Numerical Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The level of details in the final solution depends on the threshold of the topological derivative and the number of iterations. However, both obtained solutions are in qualitative agreement with 2D and 3D solutions of similar problems obtained earlier [15,16,23]. The quality of the surface of the optimal configuration is improved with Laplassian smoothing [24] post-processing step.…”
Section: Numerical Resultssupporting
confidence: 81%
“…In our recent works [15,16] we have demonstrated the application of 2D and 3D boundary element codes equipped with fast algebraic solvers to the problem of topological-shape optimization of elastic structures. However, the tools we used did not allow us to reach true scalability, and evaluate the capabilities of our approach on large problems.…”
Section: Introductionmentioning
confidence: 99%
“…The level of details in the final solution depends on the threshold of the topological derivative and the number of iterations. However, both obtained solutions are in agreement with 2D and 3D solutions of similar problems obtained earlier [23, 24,4]. The quality of the surface of the optimal configuration is improved with Laplacian smoothing [25] post-processing step (Fig.…”
Section: Cantilever Supportssupporting
confidence: 89%
“…In our earlier works [23,24] we have demonstrated that if the change in boundary configuration at every iteration is relatively small (Fig. ( 5) (B)), one can use fast update techniques for the volume and surface solutions, which would be faster than full re-computation of the BVP.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation